PERSEPSI PENGGUNA JASA PENERBANGAN TERHADAP PELAYANAN MASKAPAI PENERBANGAN GARUDA INDONESIA DI KOTA BANDA ACEH - Nadiya - (Jurnal Ilmiah Manajemen Muhammadiyah Aceh, 2012)
To determined whether the service quality of aviation is good can be seen from the ability of the service in achieving the expectation of the customer. This study aims to identify the difference between the expected service and the reality perceived by the customer in relation to the service of Garuda Indonesia airlines in Banda Aceh City.            This study used 99 customers of Garuda Indonesia Airline as the sample which is drawn by applying purposive sampling technique. Data was gathered by using questionnaire and analysis by using statistic tool, average differentiation test (t-test).            The result of statistic test shows t value is greater than the value of t-table. Thus, Ha is accepted while Ho is rejected which means there is average differentiation between the expected service and the perceived service of Garuda Indonesia’s customer            Generally, the customer has relatively good assessment towards the quality of Garuda Indonesia airlines. However, they still hope for better service in order to remains the gap between the expectation and the perceived service. Therefore, it is demanded for the management of Garuda Airlines to improve their provided service quality. Key words: User percepcion, Airline Service and Garuda Indonesia Banda Aceh